Turismo afetivo e conjugalidades em Natal: deslocamentos, família e gênero na contemporaneidade - Medeiros, Maria das Graças Lucena de (2010)
The socioeconomic and technological processes that you/they were deepened starting from the seventies of the century XX, they affected the social institutions, as the marriage and the family. The fragmentation, the efemeridade and the chaotic, although they have always been characteristic of the modern experience, they increased violently of intensity in a world context that would become globalizado. In this study a side of the effects of the Tourism Affectionate that explicit the rebuilding of affectionate family arrangements is unmasked between foreign men and Brazilian women, differing of the Sexual Tourism, that he/she understands Brazilian atraídas for the marriage promises or offers of international visitors' job in Europe. The analysis of results regarding the relationship between conjugalidade and social change as well as the one that concerns the dynamics, paths, conjugalidade forms and to the gender, they constitute other problematic nuclei approached in the investigation. One works with the hypothesis, that, the relationships affectionate-matrimonial interculturais among foreigners and Brazilian, it includes from the couple's" "harmonious and concrete search, that he/she understands the choice for a stable relationship with person of different culture, until the alteration of family contexts, considering the cultural implications, politics and of papers in the gender relationships. The field work based on qualitative interviews with foreign men and Brazilian women, that you/they reconstituted family arrangements, residents in Rio Grande do Norte, more precisely in Natal. It is ended that the European man passed to have prejudice in relation to the European woman's emancipation. The "sexual frigidit" of the Europeans, the sexual "heat of the Brazilian", the aversion of the Europeans in assuming the feminine paper of lady-of-house is interpreted as an absolute die in the speeches of the foreign informers, configuring the subject of the sexuality, sexual division of the work and cultural dominance.